Adherence to weekly anal self-examination among men who have sex with men for detection of anal syphilis - Aung, Ei T.; Fairley, Christopher K.; Ong, Jason J.; Phillips, Tiffany P.; Tran, Julien; Chen, Marcus Y.; Maddaford, Kate; Chow, Eric P. F. (Frontiers in Medicine, 2022)
Background Men who have sex with men (MSM) practicing exclusively receptive anal sex are more likely to present with secondary than primary syphilis, implying primary anorectal lesions may be missed. If men could detect anorectal lesions by regular anal self-examination, the duration of infectiousness could be reduced. We aimed to examine adherence to weekly anal self-examination. Method We conducted a longitudinal feasibility study examining the adherence to weekly anal self-examinations among MSM attending a sexual health clinic in Melbourne, Australia between December 2020 and June 2021. Adherence to weekly anal self-examinations over 12 weeks was assessed from a logbook and 4-weekly surveys. Participants who identified abnormalities in their anus were recommended to seek medical review. Results Of the 30 men who completed the study, anal self-examination was performed at least weekly for 308 of 360 person-weeks (86% of the weeks, 95% CI: 82-89). The mean adherence was 3.6 (95% CI: 3.3-3.9) examinations per four-weeks per person in Weeks 1-4, 3.5 (95% CI: 3.1-3.8) in Weeks 5-8 and 3.3 (95% CI: 2.9-3.7) in Weeks 9-12 (Ptrend=0.06). Six men (20%) were seen for medical review after they identified abnormalities, whilst eight men (27%) reported abnormalities, but did not seek medical review. No participants were diagnosed with syphilis. Conclusion We conclude that men adhered well to weekly anal self-examination. Therefore, it is feasible to trial this as a routine practice among MSM. Future studies should investigate possible reductions in adherence over time and ways to increase medical review for abnormalities that men find.